2016
DOI: 10.1002/ajmg.b.32418
|View full text |Cite
|
Sign up to set email alerts
|

The impact of CACNA1C allelic variation on regional gray matter volume in Chinese population

Abstract: The SNP rs1006737 in CACNA1C gene has been significantly associated with psychiatric disorders (e.g., schizophrenia and bipolar disorder) in European populations. In Han Chinese, rs1006737 is also strongly associated with schizophrenia, although the effects of the psychosis risk SNP on related brain functions and structures in this population remain unclear. Here, we examined the association of rs1006737 with gray matter volume in a sample of 278 healthy Han Chinese. A whole-brain voxel-based morphometry (VBM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…10,11 Among these characteristics, the risk allele of rs1006737 polymorphism in the CACNA1C gene is of particular interest because it is associated with a positive effect in grey matter (GM) density. 10,12,13 CACNA1C is a gene that encodes for the transmembrane α 1C subunit of the L-type voltage-gated calcium channel (LTCC) nominated Ca V 1.2, which facilitate transient activation of inward calcium that regulates the transcription of calcium-dependent genes with neurotropic functions such as brain-derived neurotrophic factor (BDNF). 10,14 A single nucleotide polymorphism (SNP) of CACNA1C has been associated with BD with genomewide significance, the risk variant consists in the presence of the A allele of rs1006737.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Among these characteristics, the risk allele of rs1006737 polymorphism in the CACNA1C gene is of particular interest because it is associated with a positive effect in grey matter (GM) density. 10,12,13 CACNA1C is a gene that encodes for the transmembrane α 1C subunit of the L-type voltage-gated calcium channel (LTCC) nominated Ca V 1.2, which facilitate transient activation of inward calcium that regulates the transcription of calcium-dependent genes with neurotropic functions such as brain-derived neurotrophic factor (BDNF). 10,14 A single nucleotide polymorphism (SNP) of CACNA1C has been associated with BD with genomewide significance, the risk variant consists in the presence of the A allele of rs1006737.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike rs1006737, rs2007044 has approximate MAFs between different ethnic populations. Moreover, the results of the effects of rs1006737 on cortical morphology were inconsistent, with some reporting changes in regional cortical volume 43 44 while others finding no difference in either the regional cortical volume or the subcortical grey matter volume 45 46 . It is worth noting that cortical volume comprises both surface area and thickness, and previous studies suggested that these two components of cortical volume are genetically and phenotypically independent 17 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Among the common SNP variants identified from the recent GWAS for example, variations in CACNA1C have been implicated as calcium signaling SNPs, found to confer the risk for schizophrenia [ 62 ]. Addressing this, several studies analyzed the calcium voltage-gated channel subunit α1 C-gene (CACNA1C) variations by the use of electrophysiological endophenotypes assessing phases of sleep in infants [ 64 ] by measuring regional gray matter volume [ 65 ], by measuring amygdale structure and/or function [ 66 , 67 ] by proton magnetic resonance spectroscopy of glutamatergic signals [ 68 ]. In the meanwhile, animal studies generate conditional knock-out mice for the analysis of calcium signaling in cellular level, linked to neuropsychiatric diseases [ 69 , 70 ].…”
Section: The New Agementioning
confidence: 99%